2019
DOI: 10.1126/scitranslmed.aaw9993
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical efficacy study targeting mPGES1 or EP4 in dogs with spontaneous osteoarthritis

Abstract: Canine studies of spontaneous osteoarthritis (OA) pain add valuable data supporting drug treatment mechanisms that may translate to humans. A multicenter, randomized, double-blind, placebo- and active-controlled study was conducted in client-owned dogs with moderate OA pain to evaluate efficacy of LYA, an inhibitor of microsomal prostaglandin E synthase-1 (mPGES1), an EP4 antagonist (LYB), and carprofen, versus placebo. Of 255 dogs screened, 163 were randomized (placebo/LYA/LYB/carprofen: n = 43/39/42/39) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
8
0
2
Order By: Relevance
“…Besides changes in different CMI scores, particularly pain scores calculated with the CBPI, were observed. This is of particular interest, since pain is a hallmark of OA, and its characterization produces valuable data that may translate to humans [21,73,74]. Individual CMI scores in THG improved for a majority of animals were observed with several of the considered questionnaires, in many cases up to the last evaluation.…”
Section: Plos Onementioning
confidence: 99%
“…Besides changes in different CMI scores, particularly pain scores calculated with the CBPI, were observed. This is of particular interest, since pain is a hallmark of OA, and its characterization produces valuable data that may translate to humans [21,73,74]. Individual CMI scores in THG improved for a majority of animals were observed with several of the considered questionnaires, in many cases up to the last evaluation.…”
Section: Plos Onementioning
confidence: 99%
“…41 Pain and functional ability are the most important parameters in the evaluation of OA treatment efficacy, with canine studies offering valuable data that may translate to humans. 16,45,56 We used several CMIs to try to capture multiple dimensions of OA, and we observed significant improvements with several of them—in some cases, up to the last evaluation moment. A previous report has described similar long-lasting effects of a single administration of platelet concentrate, 1 but further studies should be done to evaluate if different treatment frequencies can lead to better results.…”
Section: Discussionmentioning
confidence: 99%
“…Grapiprant, an EP4 antagonist, has been approved for by the FDA treating OA pain in dogs (132,133). A multicenter, randomized study demonstrated that the inhibitor of microsomal prostaglandin E synthase-1 (LYA) but not the EP4 antagonist (LYB) improved clinical signs of OA pain in dogs (134). Although there are animal model studies and clinical applications in effects of EP receptors in OA, the in vivo functions and molecular mechanisms of EP receptors in cartilage homeostasis and OA need further investigation.…”
Section: Prostaglandin Receptorsmentioning
confidence: 99%